Study of the Optimum Condition Towards the Inducing Paraffin Wax LDPE - Yaakob, Mohd Yuhazri; Sihombing, Haeryip; Perumal, Puvanasvaran (2012)
Low Density Polyethelene is a thermoplastic resin extracted from petroleum based, whereas the wax is an oily organic component that is contains of alkanes, ester, polyester, and hydroxyester. The purpose of this research is to find out the optimum conditions of the wax produced by inducing LDPE. The experiment is carried out by mixing the wax and LDPE into four new polymer compositions, in which the higher value of the tensile strength, Young’s modulus, and hardness are obtained by mixing between 90 wt. % LDPE with 10 wt. % wax, rather than compared to pure LDPE. The results are 8.896 MPa, 247.602 MPa and 50.9 respectively. However, only the strength impact that has a lower value as much as 31.38 %. By SEM analysis, the improvement of mechanical properties value examined in which the most suitable of optimal composition is 90 wt. % LDPE with 10 wt. % wax. The LDPE/wax mixture produces a new polymer and alters the properties of pure LDPE.